Variaciones diarias de parámetros ruminales y sanguíneos en vacas lecheras a pastoreo de primavera suplementadas con dos fuentes de nitrógeno no proteínico (2012)
An experiment was designed to study in grazing dairy cows supplemented with two sources of nitrogen the daily fluctuations of ruminal ammonia concentration and pH, as well as the blood markers for energy and protein metabolism. Four Holstein Frisian cows with ruminal fistulae and grazing on a spring pasture (Lolium perene, crude protein [CP] 24%; 2.9 Meal metabolizable energy [ME] kg -1 dry matter [DM]) were used in a alternated three groups design: control (GC); 135g urea d -1; 2x d -1 (GU); 150g protected urea, Optigen II d -1; 2x d -1(GUP). The experiment was distributed on three periods of 15 d each. Ruminal pH and ammonium concentration, together with plasma concentrations of energy and protein markers were determined in samples obtained before and until 16.5 hours (h) of the supplementation in days 1, 8 and 15 of each experimental period. Nitrogen supplementation induced an increase on ruminal ammonia concentration (GC= 26.7, GU=35.2 and GUP= 30.5 µmol/L) remaining the pH unchanged, meanwhile plasma urea (GC= 5.68; GU=6.49 and GUP= 6.28 µmol/L) and lactate (GC= 0.67, GU=0.81 and GUP= 0.68 µmol/L) concentrations increased in the GU and GUP The effects were less intensive in GUP who also had the lower plasma non esterified fatty acids (NEFA) concentrations (GC= 99.5, GU=79.9 and GUP= 73.1 umol/L). All ruminal and plasma metabolites, with the exception of urea and lactate, show significant daily variations mostly during the morning time, some increasing (ruminal ammonia and plasma ßOH-butirate) other decreasing (ruminal pH, plasma glucose and NEFA), being lest variables most stable after 11 AM. It can be established that a supplementation with 61.5 g/d of nitrogen as urea or protected urea in dairy cows at pasture increases ruminal ammonia concentration meanwhile pH values remains unaffected and increases plasma concentrations of urea and lactate. Beside, NNP supplementation did not affect daily fluctuations of the ruminal and plasma metabolites with the exception of rumen ammonia and plasma urea concentrations.